Penggunaan Internet sebagai sumber informasi dalam penyusunan karya ilmiah Siswa SMA Negeri 8 Yogyakarta - Ezra Putranda Setiawan; Ismurjanti Ismurjanti (Jurnal Kajian Informasi dan Perpustakaan, 2018)
Currently, the internet is one of the essential and user-friendly sources of information, even by students at the school. On the other hand, internet users also run the risk of obtaining inaccurate information or hoaxes. This study aimed to determine the behavior of using the internet as a source of information by Senior High School students (SMA), considering high school students began to be exposed to the internet when writing simple research reports. The research method used was documentation with a quantitative approach, namely by observing some written works of students from grade X (first year) of the State Senior High School 8 Yogyakarta in the 2016/2017 and 2017/2018 school year. The student's essay consists of three disciplines, namely biological science, engineering, and technology, as well as social science and humanities. The study focused on sources of information from the internet used in the scientific papers. Each paper’s list of reference was analyzed by grouping internet citations. Results showed that from 166 sample papers, the internet dominated the reference sources listed in the bibliography, with a percentage of around 60%. The types of internet sites that were widely cited by students were blogs, repositories, and general websites. More than 95% of sites used were in the Indonesian language. In conclusion, senior high school students need further assistance in accessing the internet, primarily to identify valid sources of information and avoid dubious information sources.